2020
DOI: 10.1016/j.yexmp.2019.104362
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-2 in cervical cancer development

Abstract: Increased expression of insulin-like growth factor binding protein 2, IGFBP-2, is associated with many cancers, though its role in cervical cancer is unclear. The aim of this study was to investigate the expression of IGFBP-2 protein and the transcriptomics profile of genes involved in the IGF signaling pathway during cervical cancer development. Design: Immunohistochemical expression of IGFBP-2 protein was semi-quantitatively assessed in tissue microarrays containing 9 normal cervix, 10 low grade cervical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…PTen, an important tumor suppressor gene, is one of the most commonly deleted or mutated tumor suppressors in a variety of types of human cancer, including breast (33), prostate (34), and cervical cancer (35). PTen inactivates the Pi3K/aKT/mTor signaling pathway, which is involved in an abundance of essential cellular processes, such as cell growth, differentiation, proliferation and migration; most of these processes have also been associated with cancer progression (36).…”
Section: Discussionmentioning
confidence: 99%
“…PTen, an important tumor suppressor gene, is one of the most commonly deleted or mutated tumor suppressors in a variety of types of human cancer, including breast (33), prostate (34), and cervical cancer (35). PTen inactivates the Pi3K/aKT/mTor signaling pathway, which is involved in an abundance of essential cellular processes, such as cell growth, differentiation, proliferation and migration; most of these processes have also been associated with cancer progression (36).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-2 is reported to be a "dark horse" physiologically and pathologically. IGFBP-2 expressions have been shown to change in a variety of diseases, such as malignancies (28,29), those related to metabolism (30) immune-related diseases (31), and cardiovascular disease (32,33). Increased expression of IGFBP-2 increased intracellular hydrogen peroxide activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, IGFBP-2 has also been demonstrated to interact with integrins to exert oncogenic effects that promote cell proliferation and invasion and suppress apoptosis. Specifically, studies have shown that IGFBP-2 is associated with metastasis and uses integrin-dependent mechanisms to reduce cell adhesion and promote invasion, suggesting that IGFBP-2 has IGF-independent oncogenic effects (52)(53)(54). By contrast, IGFBP-3 is known to protect against cancer via the p53-mediated activation of apoptosis.…”
Section: Igf Axis In Cervical Cancermentioning
confidence: 99%